Comparison of Knowledge and Performance between Faculty Members and PhD Students in Personal Information Management: Presenting an Instructional Model based on Lifelong Learning - Leila Abdolahi; Iman Tahamtan; Behnam Abdollahi; Nida Abdollahi (Tabriz University of Medical Sciences, 2012)
Introduction: Health care professionals deal with a large amount of information as they usually have various educational, scientific, clinical and administrative responsibilities. In this study we tried to investigate the knowledge of Iranian faculty members and PhD candidates of Tehran University of Medical Sciences about Personal Information Management (PIM) in order to present an instructional model to improve PIM skills. Methods: We conducted semi-structured interviews with a purposive snowball sample of 40 Iranian faculty members and PhD candidates of Tehran University of Medical Sciences. We used N8 to codify and analysis interview concepts. Results: Participants had little knowledge about how to manage their personal information. The use of PIM was in low rate among participants. Faculty members were more successful in organizing and retrieving personal information; while PhD candidates were more skilled in acquiring and keeping personal information. Conclusion: PIM is the missing link in the medical education in which various spectrums of instructional techniques is needed for the prosper implementation and usage of PIM in the medical field. We suggested an instructional model based on learning theories to educate and improve participants' knowledge and skills in PIM.